Disclosure of Corporate Social Responsibility, Firm Size, and Capital Intensity: Effects on Tax Avoidance Practices - Nurianti, Baiq Gendis; Effendy, Lukman (Journal of Finance and Business Digital, 2024)
This study examines the effect of CSR, firm size, and capital intensity on tax avoidance practices using a quantitative approach. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. Using purposive sampling, 90 companies met the criteria. Panel data regression analysis was conducted using E-Views 12. The results show that CSR and firm size have no significant effect on tax avoidance, while capital intensity has a positive and significant relationship, indicating that a higher proportion of fixed assets is associated with increased tax avoidance. The limitations of this study include the scope of variables and methods, so future research needs to explore additional variables and use a more comprehensive approach.